Relationship between integrated communication effectiveness and employee-based brand equity – mediating role of psychological contract fulfillment. Issue 6 (7th May 2021) - Deepa, R.; Baral, Rupashree
Abstract : Purpose: This study aims to expand the emerging body of literature on employer branding from the current employee perspective. It proposes that effective integrated communication helps an organization fulfill its employer value proposition or employment value proposition (EVP). A firm that fulfills its brand promise in terms of EVP will derive employee-based brand equity (EBBE) benefits. Integrated communication is effective when employees experience coordination and consistency in brand communication. This influences their perception of psychological contract fulfillment (in terms of EVP attributes), which results in positive employee behavior in the form of EBBE benefits. Design/methodology/approach: The study draws insights from the signaling theory and psychological contract literature which is based on the social exchange theory. The literature on integrated communication, employer branding and internal branding was reviewed to propose the relationships between the variables of interest. Data was collected using a questionnaire survey on 520 employees from the information technology (IT)-business process management industry in India, which is a customer-oriented industry known for its exemplary employer practices. Findings: The findings suggest that integrated communication effectiveness impacts the perceived fulfillment of EVP attributes and EBBE. Again, the fulfillment of the relational value dimension of EVP attributes partially mediates the relationship between integrated communication effectiveness and EBBE. Originality/value: This study is one of the first to explore employees' perception of integrated communication effectiveness and fulfillment in terms of EVP attributes as antecedents to EBBE.